Multicultural or Assimilationist Education: Contact Theory and Social Identity Theory in Israeli Arab–Jewish Integrated Schools. (19th September 2018) - Shwed, Uri; Kalish, Yuval; Shavit, Yossi
Abstract: We compare the predictions of contact theory with those of social identity theory (SIT), as they pertain to intergroup relations between Jews and Arabs in multicultural and assimilationist schools. In accordance with contact theory, it can be assumed that multicultural schools would promote interethnic friendships as compared to assimilationist schools. According to SIT, however, multicultural schools, in which ethnic identity is constantly acknowledged and therefore salient, would be expected to be a hindrance to interethnic friendships. We collected and analysed student networks in 61 integrated classrooms and compared the extent to which Arabs and Jews prefer same-ethnic over interethnic friendships in multicultural and assimilationist schools. We analysed the data using graph-level segregation indices, as well as exponential random graph models. Contrary to expectations from contact theory, we found a much larger degree of ethnic segregation in friendship networks in multicultural than in assimilationist schools. Findings are robust to various methods of analysis and alternative explanations. Our results challenge the assumptions that multicultural education is conducive to intergroup contact. The policy implications of these findings are discussed.